Technological interventions in European dementia care: a systematic review of acceptance and attitudes among people living with dementia, caregivers, and healthcare workers - Sorrentino, Michele; Fiorilla, Claudio; Mercogliano, Michelangelo; Esposito, Federica; Stilo, Irene; Affinito, Giuseppina; Moccia, Marcello; Lavorgna, Luigi; Salvatore, Elena; Maida, Elisabetta; Barbi, Elisa; Triassi, Maria; et al. (Frontiers in Neurology, 2024)
Background Alzheimer’s and other neurodegenerative forms of dementia affect 8 million Europeans. Assistive technologies are suggested to reduce the burden of care and improve the quality of life of person living with dementia. Nonetheless, the acceptance and attitudes toward technological interventions pose challenges not only for people living with dementia and caregivers but also for healthcare workers. This review specifically aims to investigate how these key groups perceive and accept technology in European dementia care settings. Methods This systematic review was conducted to identify studies, published between 2013 and 2023, that examined the acceptance and attitude of assistive technologies in Alzheimer’s and other dementia European settings, following the PRISMA guidelines. Rayyan AI was used for data extraction, and bias was assessed using the Mixed Methods Appraisal Tool. Results Among the 1,202 identified articles, 13 met the inclusion criteria, revealing a prevailing positivity toward technological interventions in dementia care. Nonetheless, several barriers to adoption, including technological unfamiliarity, and specific dementia-related symptoms that complicate usage were identified. They also unveiled varying attitudes, influenced by factors such as familiarity with technologies, perceived usefulness, and the broader context of the COVID-19 pandemic which accelerated telemedicine and digital solution acceptance during restricted mobility and social distancing. Conclusion Understanding attitudes toward technology in dementia care is crucial as it influences the adoption and utilization of tech-based interventions, impacting symptom management and quality of life. Addressing these attitudes through tailored interventions and education can enhance well-being and quality of life for people living with dementia, caregivers, and healthcare professionals.